Biar Dhanyang yang Bicara: Film Spiritual dan Pesan Substansial dalam Kolaborasi Produksi Film Tetangga - Tito Imanda (Universitas Muhammadiyah Yogyakarta, 2018)
This paper explores methods in making sure a film can make a statements to its audience, in this case to talk about true problems: local identities and atural resources, through non-realistic subjects: the spirits of the village. It focuses on film collaboration with a Javanese traditional performance group adapting their work to film. The project has both practical and research goals. The practical goal is to collaborate with a traditional performance from a rural area, and help facilitate their exploration of a new medium to express their narrative, aesthetic and cultural messages through film. On the other hand, the research goal of this project is to record, to understand, and to analyze this process, while laying the groundwork for further collaborations and researches in other contexts and with different communities. What so important is the exploration of the adaptation process of performance arts to film, and how the years of collaboration shapes this process and its products. When we look closely at the aesthetics of the films produced, we observed how they represent the group’s and the village’s culture, and the members’ and the villagers’ identities as well as the new set of film aesthetics that emerged from the collaboration.